Impact of Cadherin-1 Mutation Status on Gene Expression and Co-Expression Networks in Stomach Adenocarcinoma - Pazarcı, Perçin (Scientific Reports in Medicine, 2025)
Objective: This study aims to explore how cadherin 1 (CDH1) mutation status influences gene expression and co-expression networks in Stomach Adenocarcinoma (STAD). By examining frequently mutated genes, we assess transcriptomic alterations and potential molecular rewiring associated with CDH1 mutations. Method: Somatic mutation profiles and RNA-seq data for STAD patients were obtained from The Cancer Genome Atlas (TCGA). The 20 most frequently mutated genes were identified. Samples were stratified into CDH1-mutated (CDH1+) and non-mutated (CDH1−) groups. Gene expression differences were analyzed using the Wilcoxon rank-sum test. Spearman’s correlation was used to construct gene co-expression networks for each group, with significance defined as FDR-adjusted P≤0.05 and |ρ| > 0.5. Results: Seven genes showed significant differential expression between CDH1+ and CDH1− tumors. Among these, FAT3, SYNE1, ZFHX4, FAT4, and HMCN1 were upregulated in CDH1+ cases, while PCLO and DNAH5 were downregulated. Co-expression network analysis revealed 47 significant gene-pair correlations in CDH1+ tumors versus 19 in CDH1−. Conclusion: CDH1 mutation status in STAD is associated with distinct gene expression profiles and co-expression patterns, particularly involving genes related to cell adhesion and cytoskeletal organization. These findings highlight the broader impact of CDH1 alterations beyond E-cadherin loss and suggest candidate genes and pathways that may serve as biomarkers or therapeutic targets in CDH1-mutant gastric cancer.